2021
DOI: 10.21203/rs.3.rs-420056/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep learning shows declining groundwater levels in Germany until 2100 due to climate change

Abstract: In this study we investigate how climate change will directly influence the groundwater resources in Germany during the 21st century. We apply a machine learning groundwater level prediction framework, based on convolutional neural networks to 118 sites well distributed over Germany to assess the groundwater level development under the RCP8.5 scenario, based on six selected climate projections, which represent 80% of the bandwidth of the possible future climate signal for Germany. We consider only direct meteo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…This finding is also in accordance with other studies with different modelling approaches, which showed that direct climatic influences on groundwater levels are rather low and account for only a small part of the falling groundwater levels (e.g. Alfaro et al 2017;Wunsch et al 2021).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is also in accordance with other studies with different modelling approaches, which showed that direct climatic influences on groundwater levels are rather low and account for only a small part of the falling groundwater levels (e.g. Alfaro et al 2017;Wunsch et al 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the decrease in the GWL in the future period can be related to the increase in temperature and evaporation. Our result is consistent with the results of (Chang et al, 2015;Arkoç, 2022;Wunsch et al, 2022).…”
Section: -2064supporting
confidence: 93%
“…Their results showed the average annual temperature will increase and the amount of rainfall will decrease. The deep learning method was used to project GWL in Germany until 2100 under climate change (Wunsch, Liesch and Broda, 2022). The results of using ANN neural network and NARX model indicated decreased in GWL.…”
Section: Introductionmentioning
confidence: 99%
“…The code necessary to reproduce our results is available on GitHub. 60 Received: 13 April 2021; Accepted: 11 February 2022;…”
Section: Data Availabilitymentioning
confidence: 99%